Pathomorphological analysis of the qualitative composition of the inflammatory infiltrate around the pilosebaceous unit of the scalp in perifolliculitis capitis abscedens et suffodiens - O. V. Poslavska; O. L. Statkevych; T. V. Sviatenko; I. S. Shponka (Patologìâ, 2025)
Perifolliculitis capitis abscedens et suffodiens (PCAS) or Hoffman’s disease is considered a rather rare therapeutically complex purulent skin disease of unknown etiology. An active search for information regarding the qualitative and quantitative composition of the inflammatory infiltrate in PCAS, which could become a source for understanding the pathogenesis of this disease, revealed a lack of studies using the immunohistochemical staining method and authoritative recommendations on the interpretation of the obtained histological changes in punch biopsies for further treatment.